Type 1 CD4(+) T-Cell Help Is Required for Induction of Antipeptide Multispecific Cytotoxic T Lymphocytes by a Lipopeptidic Vaccine in Rhesus Macaques - Mortara, Lorenzo (American Society for Microbiology, 1999)
We have optimized the induction of antiviral cytotoxic T lymphocytes (CTL) in rhesus macaques by a lipopeptide vaccine containing seven peptides from simian immunodeficiency virus (SIV) Nef and Gag proteins and a strong T-helper peptide from tetanus toxoid (TT) that is promiscuous in humans (peptide TT 830-846). Two of the eight immunized macaques showed T-helper (Th) cell proliferation and a specific synthesis of gamma interferon in response to TT 830-846 peptide. They also showed multispecific cytotoxic activity against three to five of the immunizing SIV peptides. These results show the importance of a strong specific type 1 Th response for inducing a multispecific CTL response in vivo, which is essential for the development of an anti-human immunodeficiency virus vaccine.